Abstracts 2015
DOI: 10.1136/injuryprev-2015-041654.26
|View full text |Cite
|
Sign up to set email alerts
|

26 Evaluating access to prehospital care for traumatic brain injury patients in a resource limited setting: focus on prehospital transport

Abstract: Prehospital factors recorded include time, distance and cost. Multivariable regression analyses evaluated the effect of prehospital factors on unfavourable patient TBI outcome, in-hospital factors and demographics were controlled for. Unfavourable outcome was defined as Glasgow Outcome Score<5 on discharge or death.RESULTS: Road traffic injuries were the most common mechanism of injury (67.1%). The majority of patients were referred from other facilities in and around the region (62.3%), with 23% from the loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
2
3
0
Order By: Relevance
“…In this study, we found that once severe illness was recognized, few participants continued home care except as a stopgap measure while gathering resources for consultation with an allopathic or traditional practitioner. In the case of injury, our findings are consistent with other East African studies reporting that few injury victims receive care at the scene of accidents or en route to a health facility, despite lengthy transports [ 39 – 41 ]. In keeping with prior studies, participants reported lack of first aid skills and supplies and expressed a desire for training [ 35 , 36 , 42 , 43 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this study, we found that once severe illness was recognized, few participants continued home care except as a stopgap measure while gathering resources for consultation with an allopathic or traditional practitioner. In the case of injury, our findings are consistent with other East African studies reporting that few injury victims receive care at the scene of accidents or en route to a health facility, despite lengthy transports [ 39 – 41 ]. In keeping with prior studies, participants reported lack of first aid skills and supplies and expressed a desire for training [ 35 , 36 , 42 , 43 ].…”
Section: Discussionsupporting
confidence: 90%
“…Many participants were left with no other option but to use less-safe forms of transport like motorcycle taxis. Multiple studies on health care seeking in Uganda and other countries in SSA have also identified transportation as a key cause of delay [ 35 , 36 , 39 , 42 , 47 , 53 , 54 ]. An unpublished study by the GEC Research Team conducted at this study site found that the distance from the patient home to the ED significantly impacted patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that once severe illness was recognized, few participants continued home care except as a stopgap measure while gathering resources for consultation with an allopathic or traditional practitioner. In the case of injury, our findings are consistent with other East African studies reporting that few injury victims receive care at the scene of accidents or en route to a health facility, despite lengthy transports [39][40][41]. In keeping with prior studies, participants reported lack of first aid skills and supplies and expressed a desire…”
Section: Actions To Takesupporting
confidence: 88%
“…As data collection was based in a large, tertiary teaching hospital, the number found in our study could be higher than what would be observed at a lower level hospital. Free ambulance transport could have also contributed to the higher proportion of ambulance utilization observed in our study, as cost of ambulance transport has been cited as a barrier to usage in other resource-limited settings [ 25 , 27 , 31 ].…”
Section: Discussionmentioning
confidence: 92%
“…Our primary method of data collection was through a questionnaire administered by native research assistants fluent in English ( S2 File ) and Sinhalese. The questionnaire was developed through combining the World Health Organization’s Injury Surveillance form, Surgeons OverSeas Assessment of Surgical Need Version 3.0, and two other questionnaires from other studies that had similar objectives but were conducted in different settings [ 19 , 23 – 25 ]. Survey questions were adapted to the local context after input from local physicians.…”
Section: Methodsmentioning
confidence: 99%